Pemanfaatan Rizobakteri Penghasil Indole Acetic Acid Sebagai Agens Penginduksi Ketahanan Tanaman Tembakau Terhadap Cucumber Mosaic Virus (CMV) - Ni Luh Gede Sriyanti; Khamdan Khalimi; I Gede Rai Maya Temaja (Journal of Agricultural Science and Biotechnology, 2019)
Tobacco is a high economic value commodity, in order to meet the demand for tobacco in the market it requires good quantity and quality. One of the diseasethat often causes harm to tobacco is Cucumber Mosaic Virus (CMV). The utilization of indole acetic acid (IAA)-producing rhizobacteria can be used to increase plant growth and resistance from pathogenic infection. The aim of this study was to determine the effectiveness of IAA producing rhizobacteria formula in increasing the growth of tobacco plants in greenhouses, and to determine the effectiveness of rhizobacterial formulations in increasing tobacco plant resistanceagainst the infection of CMV. Identification of compounds in tobacco leaves that infected with CMV was carried out to determine the effectiveness of rhizobacteria in inducing plant resistance. Compound analysis was carried out using Gas Mass Chromatography Spectroscopy (GCMS). The effectiveness of rhizobacteria in increasing plant growth and resistance was conducted in a greenhouse. Based on the results of the study, four of IAA-producing rhizobacteria isolates were Stenotrophomonas maltophilia Sg3, Proteus mirabilis BjB17, Bacillus thuringiensis TNJbx3.3, and Bacillus cereus GR12, all the rhizobacterial isolates were effective in increasing plant height, leaf number, leaf chlorophyll content, wet weight and dry weight leaf. Based on the results of the rhizobacterial effectiveness test, all rhizobacterial isolates were effective in increasing plant resistance as indicated by a lower intensity of infection. Based on the analysis of the tobacco leaves compounds content showed that rhizobacteria S. maltophilia Sg3 and P. mirabilis BjB17 were able to induce resistance to tobacco plants by forming antiviral compounds namely 2-Naphthalene-sulfonic acid and rhizobacteria Bacillus cereus GR12 can stimulate the formation of 1-Naphthalene-sulfonic acid compounds and 2-Naphthalenesulfonic acidin tobacco as a form of induction of resistance to CMV infection.